TEKNIK PEMODELAN UNTUK MENINGKATKAN KETERAMPILAN MENULIS TEKS CERITA INSPIRATIF SISWA KELAS IX SMPN 1 KASIHAN - Nurweni, Riyanti Puji (UNIVERSITAS PGRI YOGYAKARTA, 2023)
This study aims to improve the writing skills of grade IX A students of SMP Negeri 1 Kasihan semester 2 of the 2022/2023 academic year on the material of writing inspirational story texts through modeling techniques. This type of research is classroom action research with a research subject of 32 students. The research procedure is carried out with the stages of planning, action, observation and reflection. The implementation time starts from January to March 2023. The study consisted of two cycles and was carried out in four meetings. Data collection techniques are carried out by means of observation, questionnaire, and document analysis. Data analysis is carried out quantitatively and qualitatively. The results showed that modeling techniques given inspirational story model texts entitled